Thermal requirement and phenological development of different grape varieties under South-Western Punjab - Gupta, Navjot; Gill, K.K.; Babuta, Ritu; Gill, MIS; Arora, N.K. (Annals of Agricultural Research, 2016)
A field experiment was conducted to work out relationship between heat unit requirement and phenophases of 15 grape varieties during the years (2008 and 2009) at Punjab Agricultural University, Regional Research Station, Bathinda (Punjab). All the phenological stages i.e., bud burst, sprouting, panicle initiation and anthesis took less number of days, (during the year 2009), while the fruit set and fruit ripening was earlier during the year 2008. The varieties Madeliene Anguvine, Banquiabyad, Beauty Seedless and Perlette ripened about 30 to 60 days earlier than the late ripening varieties viz., Arka Shyam and Arka Kanchan. For all the phenological stages, the grape varieties under study accumulated more heat units (mean value) during the year 2009 (1720.4 °C day) as compared to the year 2008 (2135.5 °C day). Early maturing varieties consumed lesser heat units for fruit ripening, as compared to late ripening varieties. In both the years, the average fruit yield was observed maximum in Perlette (31.57t/ha) followed by Cardinal (29.87t/ha) while the Ruby Red, Bharat Early and Delight were among the lowest fruit yielding varieties. The mean heat use efficiency was slightly higher (4.41 t/ha/°C) during the year 2008 as compared to year 2009 (3.44 t/ha/°C). A significant positive correlation was found between number of days for different phenological phases and cumulative heat units.